Comparability studies of hemin from two different origins porcine and bovine in the production of Haemophilus influenzae type b (Hib) polysaccharide. (September 2020) - Beri, Suresh; Gandhi, Darshan; Sharma, Pankaj; Gundpatil, Dattatraya; Goel, Sunil; Gairola, Sunil
Abstract: Hemin is one of the critical components of medium required for growth of Haemophilus influenzae type b (Hib) organisms. It is important to have different sources of critical components to ensure continuous supply for commercial production. Regulatory bodies also recommend having multiple sources for critical components. Hemin is produced from animal blood and the main sources are porcine and bovine origin. The approved Hib vaccine of SIIPL used for immunization is produced using hemin obtained from porcine origin. The present work focuses on the comparison of the growth of organisms on a large scale using hemin from bovine or porcine origin. Purified polysaccharide obtained using bovine source is tested with respect to the set WHO specifications as recommended by regulatory bodies and compared with commercial lots of PRP obtained from using hemin of porcine source. Identical product profile and quality attributes were obtained for PRP produced using bovine hemin and the regular commercial product suggests that there is no change in the product. Hemin from bovine source can be used as a replacement for hemin from porcine source in the fermentation medium for country specific requirement of Hib conjugate vaccine as long as it meets the guidelines on TSE/BSE risk.